A high-quality chromosome-level genome assembly and annotation of the giant freshwater prawn (Macrobrachium rosenbergii) - Lingyun Yu; Haiyang Liu; Jie Wei; Wanchang Zhang; Kunhao Hong; Huarong Li; Qiaoyan Zhou; Qiyao Su; Bai Liufu; Xinping Zhu; Yakun Wang (Scientific Data)
Abstract The giant freshwater prawn, Macrobrachium rosenbergii, is native to Southeast Asia and is used in aquacultural practices worldwide. It is considered advantageous because of its rapid growth, high nutritional value, and economic benefits. As one of the three major freshwater aquaculture shrimp sources in China, a high-quality genome resource is of great significance for promoting the germplasm improvement of varieties. This study presents a high-quality chromosome-level genome assembly of M. rosenbergii that was generated by combining PacBio, MGI, and Hi-C reads. The assembled genome was 2.96 Gb in size, with a contig N50 of 0.64 Mb and a scaffold N50 of 55.76 Mb, which was positioned on 59 pseudo-chromosomes. The Benchmarking Universal Single-Copy Orthologs (BUSCO) analysis for genome assembly reached 94.37%. In total, 27,111 protein-coding genes were identified, of which 25,470 were functionally annotated. These results provide a foundation for future research into adaptive evolution, genomics, and molecular breeding in M. rosenbergii.